Use of quality models by software development mypes from Lima - Amable-Ciudad, Miriam Elizabeth (2019)
Micro and small businesses (mypes) account for 85% of the software industry. They characterize by the use of quality models for both the process and the product. In a descriptive research conducted with 80 mypes, it was observed that they used more process quality models and less product quality models, and they demonstrated to know the quality factors.